2005
DOI: 10.1063/1.1872073
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of flow structure above dimpled surfaces with different dimple depths in a channel

Abstract: Flow structural characteristics over dimple surfaces located on one wall of a rectangular channel with three different dimple depths ͑␦ / D = 0.1, 0.2, and 0.3͒ are studied experimentally. Reynolds number based on channel height Re H ranges from 2100 to 20 000, and the ratio of channel height to dimple print diameter H / D is 1.0. Presented are instantaneous flow visualization images, spectra of longitudinal velocity fluctuations, vortex pair frequency information, and time-averaged surveys and profiles of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 14 publications
5
17
0
Order By: Relevance
“…Comparing the mean velocity contours and surface visualization obtained in the present study with those of Won et al (2005) and the flow patterns observed by Ligrani et al (2001) reveals why this is so. Despite flow visualization by Won et al (2005) showing the periodic fluid shedding from the dimple center, this phenomenon is similarly not detected in their mean velocity contours.…”
Section: Surface Flow Visualizationmentioning
confidence: 87%
See 3 more Smart Citations
“…Comparing the mean velocity contours and surface visualization obtained in the present study with those of Won et al (2005) and the flow patterns observed by Ligrani et al (2001) reveals why this is so. Despite flow visualization by Won et al (2005) showing the periodic fluid shedding from the dimple center, this phenomenon is similarly not detected in their mean velocity contours.…”
Section: Surface Flow Visualizationmentioning
confidence: 87%
“…Despite flow visualization by Won et al (2005) showing the periodic fluid shedding from the dimple center, this phenomenon is similarly not detected in their mean velocity contours. The contours they obtained on the other hand are similar to those obtained in the present study, showing depressions along the dimple center.…”
Section: Surface Flow Visualizationmentioning
confidence: 95%
See 2 more Smart Citations
“…Their results showed that the dimples could produce vortex, secondary flow structure, and flow mixing, and the vortex pairs were periodically shed from the dimples and become stronger as the ratio of channel height to dimple diameter decreased. Won et al [5] studied the flow structural characteristics over dimpled surfaces located on one wall of a rectangular channel with three different dimple depths. Their results indicated that the deeper dimples ejected stronger primary vortex pairs, which could result in greater mixing, higher local levels of turbulence transport, and turbulence production.…”
Section: Introductionmentioning
confidence: 99%